Mapping the IIUM students' English language writing proficiency to the common European framework of reference for languages (CEFR) - Mohd. Khairul bin Abu Sufi (Kulliyyah of Islamic Revealed Knowldge and Human Sciences, International Islamic University Malaysia, 2017)
This research sought to identify the English language writing proficiency of International Islamic University Malaysia's (IIUM) graduating undergraduates based on two scales of language proficiency; IIUM's English Proficiency Test (EPT) and the Common European Framework of Reference for Languages (CEFR). Another primary focus of this research was to investigate the relationship between the EPT rubric and the CEFR scale of proficiency. A total of 406 graduating undergraduates from all faculties at the IIUM Gombak campus were drawn through a stratified random sampling. One instrument was developed to collect data for this research; a self-developed writing test based on the IIUM EPT Writing test component. This test required respondents to answer within a specified time and word limit. The answers were then assessed by two examiners using the EPT writing test rubric, and the CEFR writing proficiency scale (general linguistic range). An inter rater reliability test was also conducted and the results indicate that an acceptable level of agreement was achieved (=.863). The findings of the EPT test indicate that the majority (48%) of IIUM undergraduates' English language writing proficiency were at Band 6, while 31.3%, 4.9% and 0.4% scored Band 5.5, Band 5 and Band 4 accordingly. On the other hand, 0.2%, 2.4%, 12.2% of the undergraduates correspondingly scored Band 8, Band 7 and Band 6.5. When measured against the CEFR scale of proficiency for writing, a large proportion of the IIUM undergraduates (46.3%) were found to be at Level B2+, whilst 2.2%, 12.4%, 33.9 and 5.2% of the students were discovered to be at Level C2, C1, B2, B1+ respectively. The findings also revealed that a meagre 0.2% were at Level B1. From the outcomes based on the EPT rubric, this research generally asserts that IIUM students are able to write effectively despite some imprecisions, inappropriate usages and misunderstandings. Furthermore, IIUM graduating undergraduates are able to understand and utilise fairly complex language, particularly in familiar situations. Results to this study based on the CEFR writing proficiency scale (general linguistic range) exudes that IIUM graduating undergraduates could express themselves clearly without much indication of having to constrict what they wanted to articulate. This research would also affirm that there is a significant relationship (rs=.874, p=.000) between the IIUM EPT writing scores and the CEFR writing proficiency scale.